PENGARUH KECUKUPAN MODAL, KREDIT BERMASALAH DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA BANK UMUM - Vita Tiagus Marina; Marlina Marlina (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study was conducted to examine the effect of variable Capital Adequacy (CAR), Non Performing Loans (NPL) and Liquidity (LDR) to Profitability (ROA) at the Commercial Bank. The population in this study is a registered commercial bank Bank Indonesia in 2011-2013. Data obtained from Bank Indonesia and the annual report published by the bank. The study sample was obtained by using purposive sampling method, and obtained a sample of 29 commercial banks. The analysis technique used is panel data and hypothesis testing using the F test and t test with a confidence level of 5%. Simultaneous research results indicate that the Capital Adequacy (CAR), Non Performing Loans (NPL) and Liquidity (LDR) to Profitability (ROA) significantly. Partially indicates that variable Non Performing Loans (NPL) and liquidity (LDR) significant effect on profitability (ROA). R2 value in this research is 0,759526, this mean that 75,95% of ROA variable could be explained by independent variables Capital Adequacy, Non Performing Loans and Liquidity. And 24,05% is explained by other variables outside the model of this study.